Implementasi Merdeka Belajar Pada Pembelajaran Pedidikana Agama Islam Pada Tingkat Usia Dasar - Sari, Nona Kumala; Salsabilla, Riva Laila (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
This study aims to explore the implementation of the Merdeka Belajar policy in the teaching of Islamic Religious Education (PAI) at SD Al-Ittihadiyah Mamiyai Bromo, focusing on how this policy is applied, the challenges encountered, and the opportunities arising from it. The research uses a qualitative approach with a phenomenological design, involving data collection through observations, interviews with the principal, PAI teachers, and students, as well as documentation studies. The findings indicate that Merdeka Belajar has been successfully implemented by providing flexibility in learning, including student-centered methods and experiential learning. However, challenges such as teacher readiness, limited resources, and shifts in teaching paradigms were also identified. Despite these challenges, the implementation has shown positive outcomes in fostering deeper engagement with Islamic values and promoting students' character development. This study contributes to the existing literature by offering insights into the application of Merdeka Belajar in religious education, which is rarely discussed in previous research.